2004
DOI: 10.1113/expphysiol.2003.027029
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in the reflex diuresis in rabbits during pulmonary lymphatic obstruction

Abstract: The role of nitric oxide in the reflex diuresis in response to pulmonary lymphatic drainage was examined in anaesthetized, artificially ventilated New Zealand White rabbits. Pulmonary lymphatic drainage was obstructed by raising the pressure in a pouch created from the right external jugular vein. Pulmonary lymphatic obstruction resulted in a significant increase in urine flow from an initial control value of 8.9 ± 0.5 ml (10 min) −1 to 12.1 ± 0.6 ml (10 min)during lymphatic obstruction (mean ± S.E.M.; n = 17,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous investigations have suggested that the response was mediated by NO produced by n‐NOS in the renal medulla (McCormick et al 2004). The present study has shown that the reflex diuresis is abolished by intramedullary infusions of the α 2 adrenergic receptor antagonist rauwolscine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have suggested that the response was mediated by NO produced by n‐NOS in the renal medulla (McCormick et al 2004). The present study has shown that the reflex diuresis is abolished by intramedullary infusions of the α 2 adrenergic receptor antagonist rauwolscine.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, it was demonstrated that the diuresis was due to generation of renal NO. 33 There are reports which show that the renal NO generation is mediated by activation of alpha-2 receptors. 34 These studies establish that sympathetic excitation can lead to NO generation by activation of nNOS through alpha-2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of a number of uncontrolled factors in our protocol. Among them we acknowledge the lack of control of altered neuronal input to the kidneys, which would have necessitated excision of the nerve input to the organ (McCormick et al. 2004); the lack of hormonal control which with altered concentrations can change sodium and water loss as well as retention (Cowley et al.…”
Section: Discussionmentioning
confidence: 99%